Prevalence of dieting, overweight, body image satisfaction and associated psychological problems in adolescent boys - (:unkn) unknown (My University, 2006)
Purpose The aim of the present study is to examine the severity of dieting and its association with obesity, body satisfaction and psychological problems in adolescent boys. Design/methodology/approach A representative sample of 800 boys in the age group of 14–19 in Qatar was approached during the period from October to December, 2004 and 593 boys gave consent to participate in this study, thus giving a response rate of 74.1 per cent. Self‐reports were obtained from 593 teenage boys using the adolescent dieting scale (ADS), and the self‐reporting questionnaire (SRQ‐20) for psychopathology. Findings Of the studied subjects, 33.1 per cent were overweight, 10.1 per cent were extreme dieters and 37.4 per cent were intermediate dieters. Among the dieters, 34 per cent were overweight. Dieting was more likely in subjects who practiced exercise and who were perceived by peers or themselves as overweight. The extreme dieters experienced more psychological problems than the intermediate dieters and non‐dieters. Extreme dieters reported sleeping problems (58.3 per cent), tired all the time (53.3 per cent) and felt like crying more than usual (50 per cent). Television was the main source of information on diet (61.7 per cent). Originality/value The present study findings provide a strong evidence for the association between frequent dieting and overweight, body image dissatisfaction and psychological problems.